Suppression of Unstable Flow by Using Rough Surfaces at Small Mass Flow Rates in a Radial Diffuser - Salem, Hayder (2006)
A Master of Science Thesis in Mechatronics Submitted by Hayder J. Salem Entitled, "Suppression of Unstable Flow by Using Rough Surfaces at Small Mass Flow Rates in a Radial Diffuser," August 2006. Thesis Advisor is Dr. Saad Ahmed. Available are both Soft and Hard Copies of the Thesis.